2007
DOI: 10.1002/jcp.21077
|View full text |Cite
|
Sign up to set email alerts
|

Expression of key substrate cycle enzymes in rat spermatogenic cells: Fructose 1,6 bisphosphatase and 6 phosphofructose 1‐kinase

Abstract: A substrate cycle composed of phosphofructo 1-kinase I (PFK) and fructose 1,6 bisphosphatase I (FBPase) has been proposed in rat spermatids. This substrate cycle can explain the ability of glucose to induce a decrease in intracellular ATP, a phenomenon that was related to regulation of [Ca(2+)]i in these cells. In spite of the importance of this metabolic cycle, the expression and activities of the enzymes that compose such cycle have not been systematically studied in spermatogenic cells. Here, we show that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This could reflect energy substrate availability, because germ cells in the luminal compartment of seminiferous tubules are believed to rely mainly on the breakdown of lactate and pyruvate provided by Sertoli cells (38,39). Independently of OXPHOS, pyruvate import into mitochondria may serve the anabolic needs of spermiogenesis, for instance for gluconeogenesis that has been suggested to occur in round spermatids in rats (40) or as a source of Acetyl-CoA for histone acetylation (41, 42), a necessary step for the massive compaction of chromatin that occurs during spermiogenesis (43). Development of reliable in vitro models of spermatogenesis will be important in the future to allow the meticulous examination of metabolic fluxes and their role in the various spermatogenic cell types.…”
Section: Discussionmentioning
confidence: 99%
“…This could reflect energy substrate availability, because germ cells in the luminal compartment of seminiferous tubules are believed to rely mainly on the breakdown of lactate and pyruvate provided by Sertoli cells (38,39). Independently of OXPHOS, pyruvate import into mitochondria may serve the anabolic needs of spermiogenesis, for instance for gluconeogenesis that has been suggested to occur in round spermatids in rats (40) or as a source of Acetyl-CoA for histone acetylation (41, 42), a necessary step for the massive compaction of chromatin that occurs during spermiogenesis (43). Development of reliable in vitro models of spermatogenesis will be important in the future to allow the meticulous examination of metabolic fluxes and their role in the various spermatogenic cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Cell homogenates were prepared with lyses buffer (20 mM HEPES pH 7.5, 10 mM EGTA, 2.5 mM MgCl 2 ) plus 1% NP‐40 and protease inhibitors (Calbiochem, Darmstadt, Germany). Twenty micrograms of total proteins were fractionated in 4–12% SDS–PAGE, transferred to PVDF membranes and probed overnight with primary antibodies [Yáñez et al, 2007]. Following incubation with an HRP‐conjugated secondary antibody, reaction was developed using the Pierce ECL Western Blotting Substrate (Pierce Biotechnology, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
“…The authors demonstrated the liver FBPase and aldolase B expression and that the (14C) lactate uptake was followed by an accumulation of radioactive glycogen confirming an active gluconeogenic metabolism. Our data by real time PCR analysis and histochemical studies (Yañez et al, 2007(Yañez et al, , 2003, suggest that FBPase is absent in pre-meiotic cells (spermatogonia and primary spermatocytes) and sustentocytes, but it is strongly expressed in VILLARROEL-ESPÍNDOLA, F. ; MALDONADO, R.; MANCILLA, H.; RAMÍREZ, A.; VANDER STELT, K.; CERECEDA, K.; LÓPEZ, C.; CASTRO, M. A.; ANGULO, C.; SLEBE, J. C. & CONCHA, I. I.…”
Section: Gluconeogenesis and Metabolic Changes During Spermatogenesismentioning
confidence: 74%
“…We have demonstrated the existence of functional gluconeogenesis in testis and sperm in different species (human, dog and rats) by highlighting the presence of key enzymes in this metabolic pathway, such as the liver isoform of fructose 1,6-bisphophatase (FBPase), phosphofructose-1 kinase (PFK) and aldolase B (Albarracin et al; Yañez et al, 2007Yañez et al, , 2003. Rat spermatids were also able to convert lactate to fructose-and glucose-6-P, indicating that both glycolytic and gluconeogenic fluxes are present in these cells (Yañez et al, 2007. We have reported that mRNA and PFK protein levels are relatively similar in spermatogenic cells, but are more strongly expressed in human sustentocytes. In contrast, expression of FBPase is stronger in round and elongating spermatids as compared to other spermatogenic cells (Yañez et al, 2003).…”
Section: Gluconeogenesis and Metabolic Changes During Spermatogenesismentioning
confidence: 99%